Oxidative toxicity mediated oophoritis alters ovarian growth in Channa punctatus under prolonged exposure to herbicide, paraquat dichloride - Anamika Jain; Shefalee Singh; Seema Yadav; Aastha Dubey; Yashika Awasthi; Vidyanand Tiwari; Vivek Kumar; Indrani Dubey; Sunil P. Trivedi; Manoj Kumar (Scientific Reports)
Abstract Herbicide paraquat dichloride, a potent redox agent found its way to natural water bodies and influences their health; however, its impact on the reproductive health of fish is potentially less studied and requires clear investigation. This study was conducted to elucidate its effect on the gonadal health of female fish, Channa punctatus over 60 days. The 96-h LC50 of test herbicide was calculated as 0.24 mL/L for the fish under examination, subsequently, three sub-lethal concentrations were taken in addition to control for the study. The experimental methodology included assessment of oxidative stress markers, hormone levels, expression of interrelated genes, and histological analysis to ascertain the damage to the ovary. At each exposure period, a significant (p < 0.05) rise in endogenous reactive oxygen species in blood cells and activities of oxidative markers in the ovary tissue were observed in treated groups. The gonadosomatic index of the ovary and hormone concentration in plasma decreased at the highest treatment concentration. A significant (p < 0.05) change in the expression of target genes for ovary growth, inflammation, and apoptosis was observed in the treated fish. Histopathological and ultrastructural investigations of the ovary tissue revealed the occurrence of oophoritis and reduced growth of the ovary in herbicide-treated fish. The findings conclude that, herbicide paraquat dichloride causes inflammation in the ovary, in addition to its growth reduction that ultimately, poses a threat to the fish population.